Acquired Cystic Disease-associated Renal Cell Carcinoma (ACD-RCC): A Multiinstitutional Study of 40 Cases With Clinical Follow-up. (September 2018) - Przybycin, Christopher G.; Harper, Holly L.; Reynolds, Jordan P.; Magi-Galluzzi, Cristina; Nguyen, Jane K.; Wu, Angela; Sangoi, Ankur R.; Liu, Peter S.; Umar, Saleem; Mehra, Rohit; Zhang, Xiaochun; Cox, Roni M.; et al.
Abstract : The incidence of renal cell carcinoma (RCC) is known to be higher in patients with end-stage renal disease, including those with acquired cystic kidney disease due to dialysis. Acquired cystic disease (ACD)-associated RCC was recently incorporated into the 2016 WHO Classification of Tumors of the Urinary System and Male Genital Tract as a distinct entity and is reportedly the most common RCC arising in end-stage renal disease. In this study, we sought to further describe clinicopathologic findings in a large series of ACD-RCC, emphasizing histologic features, immunophenotype, clinical outcome, and patterns of disease spread. We collected 40 previously unpublished cases of ACD-RCC with mean clinical follow-up of 27 months (median, 19 mo; range, 1 to 126 mo). Mean tumor size was 2.7 cm (median, 2.4 cm), and 32 tumors (80%) were confined to the kidney (pT stage less than pT3a). International Society of Urological Pathology grade was 3 in 37 cases (92.5%), grade 2 in 1 case (2.5%), and grade 4 in 2 cases (5%). Architectural variability among ACD-RCC was common, as 39 cases (98%) showed varying combinations of tubular, cystic, solid, and/or papillary growth. ACD-RCC frequently occurred in association with other renal tumor subtypes within the same kidney, including papillary RCC (14 patients), papillary adenomas (7 cases), clear cell papillary RCC (5 cases), clear cell RCC (1 case), and RCC, unclassified type (1 case). A previously undescribed pattern of perinephric and renal sinus adipose tissue involvement by dilated epithelial cysts with minimal or absent intervening capsule or renal parenchyma was identified in 20 cases (50%); these cysts were part of the tumor itself in 5 cases (25%) and were part of the non-neoplastic acquired cystic change in the background kidney in the remaining 15 cases (75%). Of the 24 cases (60%) with tissue available for immunohistochemical stains, 19 (79%) were positive for PAX8, 20 (83%) showed negative to patchy expression of cytokeratin 7, and 24 (100%) were both positive for AMACR and negative for CD117. Fumarate hydratase expression was retained in all tumors, including those with nuclear features resembling fumarate hydratase-deficient RCCs. Of the 36 patients (90%) with available follow-up information, 4 (11%) experienced adverse events: 2 patients developed a local recurrence, 1 patient experienced multiple visceral metastases and subsequently died of disease, and 1 patient developed metastases to regional lymph nodes only. One local recurrence and the lymph node only metastasis both had an unusual, exclusively cystic pattern of growth. In summary, we present the largest clinicopathologic series of ACD-RCC to date and describe previously unreported cystic patterns of local soft tissue involvement and recurrence/metastases.